1979
DOI: 10.1115/1.3451022
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Characteristics for Inline and Staggered Arrays of Circular Jets with Crossflow of Spent Air

Abstract: Heat transfer characteristics were measured for two-dimensional arrays of jets impinging on a surface parallel to the jet orifice plate. The impinging flow was constrained to exit in a single direction along the channel formed by the jet plate and the heat transfer surface. Both mean Nusselt numbers and streamwise Nusselt number profiles are presented as a function of Reynolds number and geometric parameters. The results show that significant periodic variations occur in the streamwise Nusselt number profiles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(57 citation statements)
references
References 0 publications
2
55
0
Order By: Relevance
“…Kercher and Tabakoff 19) presented the spatially-averaged surface heat transfer coefficients beneath an array of impinging jets with an in-line arrangement, whereas the results demonstrated that the Reynolds number and the streamwise/spanwise hole spacing were the most important parameters which affected all magnitudes of the spatial-averaged heat transfer coefficients. Metzger et al 20) indicated that the in-line jet arrangement hole pattern could provide an improved heat transfer than the staggered arrangements for the Reynolds numbers from 5 × 10 3 to 2 × 10 4 . The information from the aforementioned literature provided a profound insight into the multi jet impingement.…”
Section: Local Heat Transfer Characteristics Of Multi Jet Impingementmentioning
confidence: 99%
“…Kercher and Tabakoff 19) presented the spatially-averaged surface heat transfer coefficients beneath an array of impinging jets with an in-line arrangement, whereas the results demonstrated that the Reynolds number and the streamwise/spanwise hole spacing were the most important parameters which affected all magnitudes of the spatial-averaged heat transfer coefficients. Metzger et al 20) indicated that the in-line jet arrangement hole pattern could provide an improved heat transfer than the staggered arrangements for the Reynolds numbers from 5 × 10 3 to 2 × 10 4 . The information from the aforementioned literature provided a profound insight into the multi jet impingement.…”
Section: Local Heat Transfer Characteristics Of Multi Jet Impingementmentioning
confidence: 99%
“…They found that the local heat transfer coefficients are influenced by interference from neighboring jets and the averaged heat transfer coefficient is sensitive to jet-toplate spacing only when the jet-to-jet spacing is less than five jet diameters. Metzger et al [3] compared heat transfer characteristics for inline and staggered impingement patterns. The particular impingement geometries are in the range of X/d ¼ 5 and 10; Y/d ¼ 4, 6, and 8; and H/d ¼ 1-3.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of jet-hole size and distribution, cooling channel crosssection, and target surface shape all have significant effects on the heat transfer coefficient distribution. It has been shown by Metzger, et al [7] that, multiple jets perform very differently from a single jet striking a target surface. They concluded that, for multiple jets, the Nusselt number is strongly dependent on the Reynolds number.…”
Section: Impingement Coolingmentioning
confidence: 99%